1994
DOI: 10.1287/mnsc.40.7.868
|View full text |Cite
|
Sign up to set email alerts
|

A Rigorous Computational Comparison of Alternative Solution Methods for the Generalized Assignment Problem

Abstract: Statistical experimental design and analysis is a cornerstone for scientific inquiry that is rarely applied in reporting computational testing. This approach is employed to study the relative performance characteristics of the four leading algorithmic and heuristic alternatives to solve the Linear Cost Generalized Assignment Problem (LCGAP) against a newly developed heuristic, Variable-Depth Search Heuristic (VDSH). In assessing the relative effectiveness of the prominent solution methodologies and VDSH under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(19 citation statements)
references
References 23 publications
0
18
0
1
Order By: Relevance
“…The problem that instigated our search for better branching techniques is a version of the generalized assignment problem (GAP) (e.g., Amini andRacer 1994, Ross andSoland 1975) that we call the "elastic GAP" or "EGAP." The GAP arises in a number of contexts but is described here as a minimum cost assignment of a collection of orders to delivery trucks.…”
Section: Ecb For the Elastic Generalized Assignment Problemmentioning
confidence: 99%
“…The problem that instigated our search for better branching techniques is a version of the generalized assignment problem (GAP) (e.g., Amini andRacer 1994, Ross andSoland 1975) that we call the "elastic GAP" or "EGAP." The GAP arises in a number of contexts but is described here as a minimum cost assignment of a collection of orders to delivery trucks.…”
Section: Ecb For the Elastic Generalized Assignment Problemmentioning
confidence: 99%
“…The algorithm of Amini and Racer (1994) is claimed to run slower than MTHG, but produce solutions which are closer to the optimal. It should be noted that algorithm MTHG first obtains a feasible solution and then seeks to improve it.…”
Section: An Approximate Algorithm For Gapmentioning
confidence: 99%
“…The main reference for approximate algorithms and a full discussion of the problem is Martello and Toth (1990). Recent discussions on comparative performance of algorithms is contained in Amini and Racer (1994), which also lists applications and extensions to the problem and Osman (1995), updating Osman (1990), which describes various heuristics and comprehensively surveys the field. This paper will describe a simple 'dual' type approximate algorithm for GAP which is inspired by the algorithm MTHG described in Martello and Toth (1990).…”
Section: Introductionmentioning
confidence: 99%
“…By carefully devising random instances with and without a particular property, one can test how the property impacts the performances of the two algorithms and test if one is significantly better than the other when the property is present in the instance. Studies of this type can be found in the literature, e.g., for the Bin Packing Problem [26], for the Generalized Assignment Problem [3], for the Computer Network Design Problem [32], for computing asymptotic estimates of algorithm complexity [30], for analysis of Integer Linear Programming algorithms [21], for Network Reoptimization Techniques [2], and for an analysis of the effect of the choice in starting points for Nonlinear Optimization Algorithms [15].…”
Section: Introductionmentioning
confidence: 99%